STN7 Operates in Retrograde Signaling through Controlling Redox Balance in the Electron Transfer Chain - Tikkanen, Mikko; Gollan, Peter; Suorsa, Marjaana; Kangasjarvi, Saijaliisa; Aro, Eva-Mari (Frontiers in Plant Science, 2012)
Phosphorylation of the major photosynthetic light harvesting antenna proteins by STN7 kinase balances excitation between PSII and PSI. Phosphorylation of such abundant proteins is unique, differing distinctively from conventional tasks of protein kinases in phosphorylation of low abundance proteins in signalling cascades. Excitation balance between PSII and PSI is critical for redox homeostasis between the plastoquinone and plastocyanin pools and PSI electron acceptors, determining the capacity of the thylakoid membrane to produce reactive oxygen species (ROS) that operate as signals relaying information between chloroplasts and other cellular compartments. STN7 has also been proposed to be a conventional signalling kinase, instigating the phosphorylation cascade required for coordinated expression of photosynthesis genes and assembly of the photosynthetic machinery. The absence of STN7 kinase, however, does not prevent plants from sensing redox imbalance and adjusting the stoichiometry of the photosynthetic machinery to restore redox homeostasis. This suggests that STN7 is not essential for signalling between the chloroplast and the nucleus. Here we discuss the evolution and functions of the STN7 and other thylakoid protein kinases and phosphatases, and the inherent difficulties in analysing signalling cascades initiated from the photosynthetic machinery. Based on our analyses of literature and publicly available expression data, we conclude that STN7 exerts it signalling effect primarily by controlling chloroplast ROS homeostasis through maintaining steady-state phosphorylation of the light-harvesting II proteins and the redox balance in the thylakoid membrane. ROS are important signalling molecules with a direct effect on the development of jasmonate, which in turn relays information out from the chloroplast. We propose that thylakoid membrane redox homeostasis, regulated by SNT7, sends cell-wide signals that reprogram the entire hormonal network in the cell.